The Racial Justice Dilemma: Examining the Enforcement of Capital Punishment in Contemporary Legal Systems - Nurhabibi, Nurhabibi; Pinem, Serimin; Musta'ana, Musta'ana; A. Rahman, Maimun (Institute of Education and Social Research, 2024)
This research aims to discuss the dilemma of racial justice that arises in the enforcement of capital punishment in various contemporary legal systems. Although legal principles mandate justice and equality before the law, the enforcement of capital punishment often reflects glaring racial imbalance. This study analyzes the factors causing racial disparities in the application of capital punishment, as well as its impact on public trust in the legal system. The research also investigates various reform efforts that have been proposed or implemented to address the issue of racial justice in the enforcement of capital punishment. Referring to various reports, studies, and official sources from Indonesia, it can be concluded that urgent reforms are needed to address this dilemma. Measures such as racial awareness training for legal professionals, increased access to legal aid, and a review of law enforcement policies are key to improving racial justice and rebuilding public trust in the justice system. Thus, this analysis not only provides a deeper understanding of racial justice issues in the context of capital punishment in Indonesia but also highlights the efforts needed to create a fairer, more inclusive legal system respected by all members of society.